THU0081 Amelioration of collagen induced arthritis by thrombin inhibition. (1st June 2001) - Busso, N; Marty, I; Péclat, V; Kirdaite, G; Salvi, R; So, A
Abstract : Background: The deposition of fibrin observed in arthritic joints has been proved to have a deleterious role. 1 Objectives: We wish to explore the effect of the thrombin inhibitor PEG-hirudin in the pathogenesis of the murine collagen-induced arthritis (CIA). Methods: CIA was induced in male DBA/1J mice by intradermic injection of native chicken type II collagen. PEG-hirudin (injected subcutaneously at 1 mg/kg or 0.1 mg/kg per day) was given during 16 days, starting 20 days after the first immunisation (preventive treatment) or at the onset of clinical signs of arthritis (curative treatment). Results: All the mice treated with PEG-hirudin had a significantly prolonged thrombin time compared to control mice. PEG-hirudin, administered in a preventive way, led to significantly reduced incidence and severity of CIA during most of the treatment period, as assessed by clinical scoring. Accordingly, histological features showed a significant diminution of synovial hyperplasia in PEG-hirudin-treated mice compared to untreated mice. There was also a significant down-modulation of the synovial proinflammatory IL-1b and IL-12p35 cytokine mRNAs in treated mice. Intra-articular fibrin, evaluated by immunohistochemistry, was significantly reduced in treated mice compared to control mice and was positively correlated with both clinical and histological scorings. Most importantly, once arthritis was established, there was also a curative effect of PEG-hirudin. Conclusion: PEG-hirudin prevents the onset of CIA in a dose-dependent manner and has also a curative effect on established arthritis, suggesting that thrombin inhibition may offer a new therapeutic approach in arthritis. Reference: Busso N, Péclat V, Van Ness K, et al . J Clin Invest. 1998;102:41–50